Efficient NEMO Security Management Via CAPKI. - Tat, Kin Tan; Samsudin, Azman (2007)
Network Mobility (NEMO) has gained much momentum ever since being introduced. The concept of NEMO, is actually building on top of the MIPv6 and using MIh6 as its backbone. The differences are much align at the capability of the Router being able to roam freely, hence the term Mobile Router (MR).